2011
DOI: 10.1101/gr.124784.111
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide detection of natural selection in African Americans pre- and post-admixture

Abstract: It is particularly meaningful to investigate natural selection in African Americans (AfA) due to the high mortality their African ancestry has experienced in history. In this study, we examined 491,526 autosomal single nucleotide polymorphisms (SNPs) genotyped in 5210 individuals and conducted a genome-wide search for selection signals in 1890 AfA. Several genomic regions showing an excess of African or European ancestry, which were considered the footprints of selection since population admixture, were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 80 publications
(110 reference statements)
2
95
0
1
Order By: Relevance
“…To identify these outliers, we applied a strategy analogous to one that was recently used to assess natural selection among African Americans. 21 We calculated the ancestry-biased F ST between the expected and observed allele frequency for each admixed population (Supplementary Figure 4). CNVRs in the top 0.5 percentile were regarded as ancestry-biased CNVs (Table 2).…”
Section: Genetic Architecture and Admixture Properties Of Xinjiang Pomentioning
confidence: 99%
“…To identify these outliers, we applied a strategy analogous to one that was recently used to assess natural selection among African Americans. 21 We calculated the ancestry-biased F ST between the expected and observed allele frequency for each admixed population (Supplementary Figure 4). CNVRs in the top 0.5 percentile were regarded as ancestry-biased CNVs (Table 2).…”
Section: Genetic Architecture and Admixture Properties Of Xinjiang Pomentioning
confidence: 99%
“…Detailed information about the African-American and Mexican data sets has been described in previous studies. 1,25 Briefly, the African-American data set contained 2214 AfricanAmericans and 268 samples from their three putative parental populations. The 268 samples representing the three putative parental populations consisted of 112 European samples (Utah residents with northern and western European ancestry from the CEPH collection; CEU), 112 African samples (Yoruba in Ibadan, Nigeria; YRI) and 44 Amerindian samples.…”
Section: Population Samples and Datamentioning
confidence: 99%
“…HAPMIX permits small rates of miscopying from the ancestral haplotype, modeling unphased diploid data from the admixed population with the HMM. Our simulations showed that HAMPIX performed better compared with other methods when very recent admixed population were investigated [82].…”
Section: Admixed Population and Admixture Mappingmentioning
confidence: 92%
“…Thus, some genomic regions in admixed population might show excess of a particular ancestry, possibly attributable to selection pressures after the population admixture [84]. By far, several studies have used the genome-wide data to scan for signatures of selection in admixed populations [82].…”
Section: Biased Ancestry Contribution In Admixed Populationsmentioning
confidence: 99%
See 1 more Smart Citation